2019
DOI: 10.1111/andr.12672
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation improves erectile function in patients with idiopathic vasculogenic erectile dysfunction by lowering peripheral and penile homocysteine plasma levels: a case‐control study

Abstract: BackgroundErectile dysfunction (ED) has common risk factors with many cardiovascular (CV) impairments. In view of these facts, hyperhomocysteinemia (HHcys) has been postulated for involvement in endothelial dysfunction.ObjectivesWe evaluated peripheral and penile homocysteine (Hcys) plasma levels before and after folic acid supplementation in idiopathic vasculogenic erectile dysfunction (ED) patients. Materials and methods: This study included 50 consecutive patients and 50 consecutive healthy controls that we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Dermcidin level was significantly low in the studied cohort of acne vulgaris patients and both isotretinoin regimens significantly raised dermcidin levels compared to pretreatment values. No significant difference in relapse rate over a 12-month follow-up period was noted among the two isotretinoin regimens (El Aziz Ragab, Omar, Collier, El-Wafa, & Gomaa, 2018).…”
Section: Indications Of Low-dose Isotretinoin In Dermatologymentioning
confidence: 76%
See 1 more Smart Citation
“…Dermcidin level was significantly low in the studied cohort of acne vulgaris patients and both isotretinoin regimens significantly raised dermcidin levels compared to pretreatment values. No significant difference in relapse rate over a 12-month follow-up period was noted among the two isotretinoin regimens (El Aziz Ragab, Omar, Collier, El-Wafa, & Gomaa, 2018).…”
Section: Indications Of Low-dose Isotretinoin In Dermatologymentioning
confidence: 76%
“…Very recently, folic acid administration demonstrated a significant decrease in peripheral and penile homocysteine plasma levels in Egyptian patients with idiopathic vasculogenic erectile dysfunction (Elshahid et al, ). Deficiency in folate may pose a much greater risk for the development of peripheral neuropathy, particularly patients younger than 40 years (Taverner et al, ).…”
Section: Safety Of Low‐dose Isotretinoinmentioning
confidence: 99%
“…with no abnormalities in routine investigations except decreased FA levels. In various studies, age has not been significantly different between the groups and also did not correlate with FA levels (Elshahid et al, 2020;Karabakan et al, 2016;Sansone et al, 2017;Yang et al, 2014). Study by Attia et al (2019) demonstrated negative correlations between FA levels and age.…”
Section: Discussionmentioning
confidence: 89%
“…The changes of the IIEF-5 after the folic acid administration only were reported in two articles. 23 , 24 Fixed-effect model was used to calculate the SMD owing to the no significant heterogeneity (I 2 = 0.00%, P = .645). The SMD was 1.89 with the 95%CI (1.60, 2.17).…”
Section: Resultsmentioning
confidence: 99%